Fatty Acids in Some Cooking Oils as Agents of Hormonal Manipulation in a Rat Model of Benign Prostate Cancer (Nigerian Journal of Physiological Sciences, 2019)
Summary: Anti-androgenic substances, mainly prostate 5α-reductase inhibitors, used in the treatment of benign prostatic hyperplasia (BPH) have been associated with side effects in man and animals. To reduce these side effects as well as suppress BPH development, the management of the condition has come to include dietary interventions. This study investigated the effect of some cooking oils on testosterone-induced hyperplasia of the prostate in rats. Male Sprague-dawley rats were distributed into eighteen groups (n=6) as A-R. A negative control group was injected subcutaneously with soya oil; while prostatic hyperplasia was induced subcutaneously in groups B-R with 3mg/kg testosterone daily for 14days. Group B was the positive control (BPH group) while groups C-R were also administered orally 800mg/kg of coconut, castor, canola, cottonseed, pomegranate, blackseed, sheabutter, olive oil, codliver, sardine, palm, repeatedly heated palm (RHPO), vegetable, repeatedly-heated vegetable (RHVO), sesame, and groundnut oils respectively, daily, for 14 days. Blood sample was drawn via retro-orbital sinus for the estimation of serum testosterone(T) and dihydrotestosterone (DHT) level and rats were thereafter euthanized to obtain the prostates for T and DHT determination as well as tissue weights. Data are mean ± SEM, compared by ANOVA. The oils significantly reduced the increase in prostate weight (PW) to body weight (BW) ratio induced by testosterone. Apart from the fact that all the oils reduced the PW:BW ratio, the blackseed, sheabutter, sardine, vegetable and groundnut oils suppressed the DHT level in the serum, while pomegranate, olive, RHPO reduced DHT level in the prostate compared to the BPH rats. This study suggests that blackseed, sheabutter, sardine, vegetable, groundnut, pomegranate, olive, and RHPO oils could inhibit testosterone-induced hyperplasia of the prostate and therefore may be beneficial in the management of BPH.